Effects of Ethylene Degreening on Peel Color, Physical Quality, and Chemical Content of Ambon Kuning (Musa acuminata Colla) - Ardhianata Triasmoko; Anggoro Cahyo Sukartiko; Nafis Khuriyati (Agroindustrial Journal, 2022)
The natural ripening of ambon kuning, a typical banana widely consumed in Indonesia, tends to produce a non-uniform yellowish peel color of the fruits. Some degreening techniques using calcium carbide or ethepon, although improving the peel color appearance, may pose a safety risk compared to ethylene degreening, a technique using ethylene gas, a gas naturally produced by the fruit. This study aimed to determine the effect of ethylene degreening on changes in peel color, physical quality, and chemical content of ambon kuning and determine the combination of treatment that produces the best results. Taguchi design, with two levels for each of the three treatment factors (ethylene gas concentrations of 185.2 and 277.8 ppm, storage temperatures of 16±1 and 29±1 °C, and gas exposure time of 48 and 72 hours) was applied to banana samples stored in a hermetic bag in a temperature-controlled container. Grey Relational Analysis (GRA) was applied to get the best results considering multiple performance measures: peel color (measured as lightness L*-, green -a*-, and yellow b*-values), hardness of peel and pulp, total dissolved solids, total chlorophyll, and total carotenoids contents. The best results were obtained when degreening was carried out with a gas concentration of 185.2 ppm at a storage temperature of 16±1 °C for 48 hours.